2003
DOI: 10.1002/app.11860
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of semi‐interpenetrating polymer network polystyrene cation‐exchange membranes

Abstract: Polystyrene cation exchange membranes were prepared by a PVC-based semi-interpenetrating polymer network (IPN) method. The reaction behaviors during polymerization and sulfonation in the preparation method were investigated. The prepared membranes were characterized in terms of the physical and electrochemical properties. The membranes exhibited reasonable mechanical properties (tensile strength, 13 MPa, and elongation at break, 52%) for an ion-exchange membrane with the ratio of polystyrene-divinylbenzene (DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The two absorption peaks at 1660 and 1590 cm À1 for commercial chitosan are assigned to the C@O stretch of the secondary amide and the N-H bending of the primary amine, respectively [35]. The C-H bending of trimethylammonium group is registered at 1480 cm À1 for semi-IPN-0 confirming the existence of the quaternary ammonium salt in the QCS [27], and this absorption is shielded by the stretching vibration of the skeletal aromatic rings of the PS in the spectra of semi-IPN-8 and semi-IPN-21 [28]. It is also observed that the peak corresponding to the primary amine (1590 cm À1 ) of chitosan dwindles and a new peak at around 1640 cm À1 for semi-IPN-X (X -0) membranes was recorded, indicating the change of the primary amine to the secondary amine structure due to the reactions at NH 2 sites on the chitosan chains [23].…”
Section: Production Of Qcs/ps-based Semi-ipn Membranesmentioning
confidence: 89%
See 3 more Smart Citations
“…The two absorption peaks at 1660 and 1590 cm À1 for commercial chitosan are assigned to the C@O stretch of the secondary amide and the N-H bending of the primary amine, respectively [35]. The C-H bending of trimethylammonium group is registered at 1480 cm À1 for semi-IPN-0 confirming the existence of the quaternary ammonium salt in the QCS [27], and this absorption is shielded by the stretching vibration of the skeletal aromatic rings of the PS in the spectra of semi-IPN-8 and semi-IPN-21 [28]. It is also observed that the peak corresponding to the primary amine (1590 cm À1 ) of chitosan dwindles and a new peak at around 1640 cm À1 for semi-IPN-X (X -0) membranes was recorded, indicating the change of the primary amine to the secondary amine structure due to the reactions at NH 2 sites on the chitosan chains [23].…”
Section: Production Of Qcs/ps-based Semi-ipn Membranesmentioning
confidence: 89%
“…It is also observed that the peak corresponding to the primary amine (1590 cm À1 ) of chitosan dwindles and a new peak at around 1640 cm À1 for semi-IPN-X (X -0) membranes was recorded, indicating the change of the primary amine to the secondary amine structure due to the reactions at NH 2 sites on the chitosan chains [23]. The peaks at 3025, 1600, 1500, and 1493 cm À1 in the spectra of the semi-IPN-8 and semi-IPN-21 are attributed to the stretching vibration of the skeletal aromatic ring of the PS [28]. These results demonstrate that quaternary amino groups have been effectively grafted onto the chitosan backbones to form the QCS, and the linear PS has been synthesized to form the semi-IPN system with the cross-linked QCS together.…”
Section: Production Of Qcs/ps-based Semi-ipn Membranesmentioning
confidence: 92%
See 2 more Smart Citations
“…8,9 The available substrate materials for preparing ion-exchange membranes are poly(ether ether ketone), poly(phosphazene), polystyrene, polyimide, poly(ether sulfone) (PES), polysulfone and so on. [10][11][12][13][14][15][16] It is generally agreed that cation exchange membranes should have high chemical and mechanical stability with favorable electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%